365. PROGNOSTIC COMPARISON OF LYMPHOVASCULAR INVASION AND LYMPH NODE METASTASIS IN ESOPHAGEAL CANCER PATIENTS. (24th September 2022) - Li, Kexun; Leng, Xue Feng; Nie, Xin; Liu, Kun; He, Wenwu; Wang, Qifeng; Luo, Xi; Wang, Chenghao; Wang, Kangning; Liu, Guangyuan; Wei, Xing; Li, Haojun; et al.
Abstract: The incidence and mortality of esophageal cancer are high-ranking in the world, more than half of cases occur in China. The cornerstone of treatment for resectable esophageal cancer is esophagectomy. Lymphovascular invasion and lymph node metastasis are both vital prognostic factors for patients who have been through esophagectomy. But in fact, the combined influence of these two factors on prognosis remains controversial. Samples were obtained from the Sichuan Cancer Hospital & Institute Esophageal Cancer Case Management Database (SCH-ECCM Database). We retrospectively analyzed esophageal cancer patients who underwent esophagectomy from Jan. 2010 to Dec. 2016. Patients were divided into two groups according to the postoperative pathological outcomes: patients with only lymph node metastasis were pointed into group A, patients with only lymphovascular invasion were distributed to group B. Clinical outcomes and survival data were compared using TNM stages of AJCC 8th edition. After 68.1 months of median follow-up time, 1596 patients who received esophagectomy were included. The median overall survival (OS) was 45.9 months (95% CI 38.5–53.2). Only lymph node metastasis group achieved median OS of 34.9 months (95% CI 30.7–39.1), however, only lymphovascular invasion group did not reach the median OS time. The OS at 1, 3, and 5 years were 91%, 70%, and 64% in the only lymphovascular invasion group group, respectively. In the only lymph node metastasis group, the OS rates at 1, 3, and 5 years were 82%, 49%, and 37%, respectively (HR 0.438, 95% CI 0.3074–0.624, P = 0.0012). Esophageal cancer patients with only lymph node metastasis had significantly worse OS than the patients with only lymphovascular invasion. It reveals that we should pay more attention to these risk factors, and further studies need to be done to stratify the accurate subgroups.